(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2007)
The changes in the contents of enzymes activity of the seed of three varieties of mungbean were analysed at different hour of germination. Amylase and invertase activity were tremendously increased 200-220 % and 165-175 % respectively at 24 hour of germination and decreased gradually from 48-96 hour of germination. Protease activity was remarkably increased at 24 hour then further increased upto 48 hour (131-161%) and then decreased from 72-96 hour of germination. BARIMung-3 variety showed the best result i.e the highest amount of enzymes activity among the three varieties of mungbean at 24 hour of germinaton. Bangladesh J. Sci. Ind. Res. 42(2), 213-216, 2007